GROWTH AND PRODUCTION OF COCONUT DWARF GREEN FERTIRRIGADO WITH NITROGEN AND POTASSIUM - MATIAS, Sammy Sidney Rocha; AQUINO, Boanerges Freire de; FREITAS, José de Arimatéia Duarte de (Scientia Agraria, 2010)
The nitrogen and potassium deficient in initial growth phase of coconut palm could spoil all the plant physiology resulting in production decrease. The objective of this study was to evaluate the application of nitrogen and potassium fertigation on plant development, at three, and the production of dwarf green, four years old, grown in a soil classified as Quartzipsament. The objective of this study was to evaluate the effects of applying nitrogen and potassium fertigation on plant development, at three, and the production of dwarf green, four-year-old, sandy soil in the municipality of the region Paracuru litorâncea Ceará. The work was conducted in the commercial planting of green coconut dwarf of Jiqui, in the municipality of Paracuru, (CE). The experimental design was randomized blocks, with 10 treatments consisting of five combined doses of nitrogen and potassium, according to Plan Puebla III experimental matrix model. Were evaluated the following characteristics: plant height, trunk perimeter, number of leaves, number of leaflets on the leave 3, to three years of age and number of bunch per plant, fruit number per plant, fruit weight, fruit perimeter (equatorial and polar), fruit water volume, soluble solids, with four years of age. The doses of N and K applied to the soil affected the number of clusters. The increase in N resulted in a linear increase in the variables height, circumference of the girth, leaf number and leaflet number leaf 3. The higher N rates promoted the reduction of production variables except the soluble solids. The highest doses of K2O resulted in a significant increase in the number of fruits per plant and total soluble solids.